Effect of micronization and vitamin E supplementation on ruminal biohydrogenation kinetic of whole flaked rapeseed - Zohreh Zarnegar; Saman Lashkari; Seyed Hadi Ebrahimi; Reza Valizadeh; Abbas Ali Naserian; Søren Krogh Jensen (Journal of Applied Animal Research, 2024)
The effect of heat treatment (raw or micronization) and vitamin E supplementation (0 or 200 mg/kg DM of RRR-α-tocopherol) on ruminal biohydrogenation (BH) kinetic of whole flaked rapeseed was studied using in vitro batch culture in a 2 × 2 factorial design. Experimental treatments were: whole flaked raw rapeseed without vitamin E (RR0), whole flaked raw rapeseed supplemented with 200 mg/kg DM of vitamin E (RR200), micronized whole flaked rapeseed without vitamin E (MR0) and micronized whole flaked rapeseed supplemented with 200 mg/kg DM of vitamin E (MR200). The disappearance of linoleic acid (LA), alpha-linolenic acid (LnA), oleic acid (OA), and appearance of stearic acid (SA), and C18:1 trans-11 (VA) were significantly decreased by micronization (P < 0.0001 for all). The appearance of cis-9, trans-11 conjugated linoleic acid (CLA; P < 0.0001) and C18:1 trans-10 (P = 0.01) was significantly increased by micronization. Biohydrogenation of LA (P = 0.03) and OA (P = 0.02) was significantly decreased by vitamin E. There was a tendency to reduce disappearance of LnA by vitamin E (P = 0.06). In conclusion, micronization is an effective method to protect unsaturated fatty acids (UFA) from ruminal BH. Vitamin E supplementation can be an advantageous strategy to decrease LA, LnA and OA biohydrogenation.